Comparative analysis of institutions’ evaluation methods: an application using the, ARWU, QS, RUR, and Capes - César Schotten, Paulo; Sérgio Eduardo, Antônio; Fachin, Solange; Cardoso da Silveira, Vitor (Seven Editora, 2023)
This study aimed to analyze five models of university evaluation, more precisely THE, QS, ARWU, and RUR, and compare them with a Brazilian evaluation model represented by CAPES. To achieve this goal, advanced evaluation methods have been bibliographically identified. Regarding methodology, this is a descriptive analysis as to its objective and qualitative analysis of the data. The points were analyzed concerning research, teaching, internationalization, and reputation. With the collected data we observed some similarities and differences between the models. Among the main similarities, it was emphasized that all models are used in the multi-criteria method of analysis. The differences between them are the criteria that are analyzed and the objectives that each method proposes. The research indicates limitations to the quantitative analysis of indicators and the different goals of each method. DOI: https://doi.org/10.56238/tfisdwv1-162